Towards Meaningful Interpretation of Molecular Data: Insights Gained from HMMD Challenges in Salmonella Detection for Future NGS Integration in Clinical Microbiology - Hyunji Kim; Soo Hyun Seo; Jae-Seok Kim; Kwang Jun Lee; Kyoung Un Park (Diagnostics)
Background: With advancements in molecular diagnostics, including Highly Multiplexed Microbiological/Medical Countermeasure Diagnostic Devices (HMMDs) and the impending integration of Next-Generation Sequencing (NGS) into clinical microbiology, interpreting the flood of nucleic acid data in a clinically meaningful way has become a crucial challenge. This study focuses on the Luminex xTAG Gastrointestinal Pathogen Panel (GPP) for Salmonella detection, evaluating the impact of MFI threshold adjustments on diagnostic accuracy and exploring the need for an “indeterminate” result category to enhance clinical utility in molecular diagnostics. Methods: A retrospective review of Salmonella-positive cases detected via the Luminex xTAG GPP was conducted from June 2016 to November 2023. Key metrics included patient symptoms, stool culture results, and potential infection sources. Results were analyzed using the assay’s MFI cutoffs in Versions 1.11 and 1.12. Statistical comparisons between culture-confirmed and non-confirmed cases were performed using Kruskal–Wallis tests to assess MFI value distributions. Results: Among 2573 tests, 212 were Salmonella-positive under Version 1.11, while 185 were positive under Version 1.12. Adjusting the MFI threshold in Version 1.12 reduced false positives from 40.6% to 38.4% but led to one culture-confirmed positive case being missed. Statistically significant MFI differences were observed between culture-positive and culture-negative cases, suggesting that fixed binary cutoffs may not always yield clinically accurate interpretations. Discussion: The MFI threshold adjustment decreased false positives without fundamentally improving diagnostic accuracy, highlighting the limitations of binary interpretations in HMMDs. Introducing an “indeterminate” category, especially for cases with low MFI values, could aid clinicians in integrating molecular results with patient context. This approach offers a framework for future NGS integration, where nuanced interpretation will be essential to differentiate clinically significant findings from incidental data. Conclusions: Implementing an “indeterminate” interpretation category for HMMDs could enhance clinical decision-making and refine public health surveillance by focusing on clinically relevant findings. As NGS moves toward clinical application, establishing similar interpretive standards will be essential to manage the complexity and volume of molecular data effectively.